Petrologia do batólito Sítios Novos, Domínio Poço Redondo, Sistema Orogênico Sergipano - Pinho Neto, Maurício Almeida de (2018)
The Sítio Novos Batholith (110 km2) is an NE-SW elongated intrusion, with a age of 631 ± 4 Ma, which agrees with the regional orientation, and is located in the southern region of the Poço Redondo Domain, in the Sergipano Orogenic System. This batholith is constituted by leucocratic monzogranites with allitriomorphic equigranular and inequigranular texture, and occasionally they present pegmatitic dykes. Mafic enclaves are rare. The southern region of the batholith is affected by regional shear zone and the monzogranites developing milonitic and gniassic structures. Oligoclase and albite are the plagioclase present in these granites and the microcline is occasionally pertítica. Biotite is the dominant mafic mineral and its composition indicates affinity with orogenic suites (calic-alkaline and peraluminous). Muscovite occurs in most samples. Zircon, titanite, magnetite, ilmenite, apatite, thorite, allanite and monazite occur as accessory minerals. Basanesite and barite often occupy microfractures in these rocks. The geochemistry of the monzogranites shows that they are fractionated rocks (SiO2 up to 77%), peraluminous to metalluminous and are allocated in geochemical diagrams in the field of Type I granites. The REE spectra present moderate fractionation (15 <(LaN/ YbN)<70), with negative anomaly in I indicating plagioclase fractionation. In multielementary diagrams the samples of this batholith have pronounced valleys in Nb, P, Ba and Ti, and more or less accentuated peaks in Th, Pb and Zr. This geochemical signature indicates that the magma that formed these monzogranites present orogenic signature. These monzogranites have as probable source the partial fusion of tonalitic crust.